A Self-centric Learning Methodology in Qur'anic Recitation with Tajweed using Multimedia Instructional Design Approach - Tariq Hassan Ahmed Mssraty (Universiti Sains Islam Malaysia, 2024)
The technological innovations in multimedia learning systems has transformed the learning pattern at various settings, notably, traditional learning systems have shown to be inappropriate for teaching and learning Quranic recitation based on the Tajweed rules.Based on the review of literature the students are taught Arabic Language without all vowels.Since the teaching and learning of Quranic recitation based on Tajweed is a difficult task that requires more than prior experience and knowledge of the learner in Arabic language, the present research conducted based on a few learning theories such as Mayer, Reigeluth and Vygotsky theories.This research employed a afew multimedia models of Gagne’s, Arcs’s, Mayer’s and Assure models. The main objective of this research is to determine and critically appraise the existing Arabic Teaching products available in Malaysia schools and markets that teach Arabic language and Quran by evaluating the strength and weaknesses of these products. Thisresearch has provided the method of teaching Quran recitation by adding Al-sokun in a new multimedia instructor design called Almoneer. Its main function is to motivate students to recite the Holy Quran based on Tajweed and pronounce the Alphabets with all Arabic vowels and distinguish between Quranic Recitation and Tajweed rules. This research used quantitative, qualitative and descriptive methods in collecting data. A quantitative research method based on a survey questionnaire were used to collect quantitative data from a total of 139 students that formed a treatment group and 42 students that formed the controlled group in classes 4 and 5 at Sekolah Kebangsaan Taman Kosas Ampang Selangor. Furthermore the pre-test and post-test have used as instruments in this study. The qualitative data was obtained through interviewing two Quranic teachers. Checklist and Classroom observation were used as means of qualitative data. The data was analysed by SPSS. Excel and AMOS programs.The methods used in this study were suitable in addressing al the research objectives and answering the research questions.The results showed that students who were exposed to Almoneer had out-performed the controlled group in their motivation, skills, satisfaction and increased their final grades than those who were exposed to the traditional method. The mean score of the traditional teaching group in the pre-test 48.20% whereas the post-test mean is 49.48%. The mean score of the Amoneer students pre-test is 39.26% and their post-test is 84.74%. It is evident that the Almoneer instructional learning approach should be used to improve Quran teaching and recitation learning in Malaysia schools and can be replicated to other academic subjects.